Biomonitoring of metals in blood and urine of electronic waste (E-waste) recyclers at Agbogbloshie, Ghana. (October 2021) - Takyi, Sylvia A.; Basu, Niladri; Arko-Mensah, John; Dwomoh, Duah; Houessionon, Karel G.; Fobil, Julius N.
Abstract: There is growing evidence that e-waste recyclers may be exposed to potentially high levels of metals though associations between such exposures and specific work activities is not well established. In addition, studies have focused on metals traditionally biomonitored and there is no data on the exposure of recyclers to elements increasingly being used in new technologies. In the current study, levels of metals were measured in blood and urine of e-waste recyclers at Agbogbloshie (Ghana) and a control group. Blood and urine samples (from 100 e-waste recyclers and 51 controls) were analyzed for 17 elements (Ag, As, Ba, Cd, Ce, Cr, Eu, La, Mn, Nd, Ni, Pb, Rb, Sr, Tb, Tl, Y) using the ICP-MS. Most e-waste recyclers reported performing at least 4 different tasks in decreasing order as e-waste dismantling (54%), trading/selling of e-waste (45%), burning wires only (40%), and collecting wires after burning (34%). Mean levels of blood Pb, Sr, Tl, and urinary Pb, Eu, La, Tb, and Tl were significantly higher in recyclers versus controls. In general, the collectors and sorters tended to have higher elemental levels than other work groups. Blood Pb levels (mean 92.4 μg/L) exceeded the U.S. CDC reference level in 84% of the e-waste recyclers. Likewise, blood Cd, Mn, and urinary As levels in recyclers and controls were higher than in reference populations elsewhere. E-waste recyclers are exposed to metals traditionally studied (e.g., Pb, Cd, As) and several other technology-critical and rare earth elements which previously have not been characterized through human biomonitoring. Highlights: e-waste workers are exposed to potentially high levels of diverse metals. Biomonitoring of technology critical and rare earth elements seldom done. Blood Pb, Sr, Tl and urinary Pb, Eu, La, Tb, and Tl higher in workers vs. controls. Exposures linked to different e-waste work practices.